Contribution to detonation ability of explosives - Vávra, Pavel (Univerzita Pardubice, 2006)
By investigating a set of 40 substances, a possibility has been shown of estimate of their detonation ability from the calculated detonation energy and oxygen balance. The calculations have shown that substances with detonation energies below 3 kJ cm-1 will probably be able to detonate only if their geometry exceeds the critical diameter, or the detontion will fail at all. Also discussed are the effects of density and initiation pressure.
Keywords: detonace; detonační parametry; výpočty; kyslíková bilance